Appropriateness of referral of coronary angiography patients in Sweden - Bernstein, S (1999)
OBJECTIVE—To evaluate the appropriateness of referral following coronary angiography in Sweden.  DESIGN—Prospective survey and review of medical records. PATIENTS—Consecutive series of 2767 patients who underwent coronary angiography in Sweden between May 1994 and January 1995 and were considered for coronary revascularisation.  MAIN OUTCOME MEASURES—Percentage of patients referred for coronary artery bypass graft surgery (CABG) and percutaneous transluminal coronary angioplasty (PTCA) for indications that were judged necessary, appropriate, uncertain, and inappropriate by a multispecialty Swedish national expert panel using the RAND/University of California Los Angeles (UCLA) appropriateness method, and the percentage of patients referred for continued medical management who met necessity criteria for revascularisation. RESULTS—Half the patients were referred for CABG, 25% for PTCA, and 25% for continued medical therapy. CABG was judged appropriate or necessary for 78% of patients, uncertain for 12% and inappropriate for 10%. For PTCA the figures were 32%, 30% and 38%, respectively. Two factors contributed to the high inappropriate rate. Many of these patients did not have "significant" coronary artery disease (although all had at least one stenosis > 50%) or they were treated with less than "optimal" medical therapy. While 96% of patients who met necessity criteria for revascularisation were appropriately referred for revascularisation, 4% were referred for continued medical therapy. CONCLUSIONS—Using the RAND/UCLA appropriateness method and the definitions agreed to by the expert panel, which may be considered conservative today, it was found that 19% of Swedish patients were referred for coronary revascularisation judged inappropriate. Since some cardiovascular procedures evolve rapidly, the proportion of patients referred for inappropriate indications today remains unknown. Nevertheless, physicians should actively identify those patients who will and will not benefit from coronary revascularisation and ensure that they are appropriately treated.   Keywords: coronary artery bypass graft surgery; angioplasty; quality of health care; health policy